Validating the Efficacy of a Stepwise Video Module for Conjunctival Closure - Nguyen, Geoffrey; Palmer, Jamie; Levin, Moran R.; Swamy, Ramya; Alexander, Janet (Journal of Academic Ophthalmology, 2023)
Objective The aim of this study is to describe a cost-effective and portable surgical training module for ophthalmology trainees and demonstrate its effectiveness in building confidence and reducing stress with conjunctival closure.Methods A total of 29 trainees (fourth year medical students, postgraduate year (PGY) 1 ophthalmology residents, PGY2 ophthalmology residents) participated in the module during July 2022. They completed a Pre-Module and Post-Module Questionnaire, with some questions assessing their confidence level and other questions assessing their stress level with conjunctival closure. A Likert scale of 1 to 10 was used to evaluate their level of confidence or stress (with 1 indicating low confidence or low stress and 10 indicating high confidence or high stress).Results Prior to completing the module, participants had an average conjunctival suturing skills confidence level score of 2.6 ± 1.6, which increased significantly to 5.6 ± 1.6 after completing the module (p < 0.001). Participant's stress level score with performing conjunctival closure on live patients significantly decreased from 7.5 ± 2.4 to 5.6 ± 1.5 (p < 0.001) after completion of the module. When participants were separated into two groups, participants in the PGY1 residents/medical students group had an average conjunctival suturing skills confidence level score of 2.7 ± 1.8, which rose significantly to 5.1 ± 1.5 after completing the module (p = 0.008), whereas PGY2 residents had an average conjunctival suturing skills confidence level score of 2.6 ± 1.6, which rose significantly to 5.8 ± 1.7 after completing the module (p < 0.001). Participant's stress level scores with performing conjunctival closure on live patients did not show significant results in the PGY1 residents/medical students group but significantly decreased from 7.2 ± 2.2 to 5.2 ± 1.3 (p < 0.001) in PGY2 residents. Participants agreed that the video presented was effective for learning the surgical skill and that the module was engaging and prepared them well to learn more advanced conjunctival suturing techniques.Conclusion Our surgical training module is an effective teaching tool for ophthalmology trainees to increase confidence and decrease stress about performing conjunctiva closure. It provides an opportunity for trainees to repetitively practice key surgical techniques on an inexpensive and reusable training model.
Keywords: COVID-19; ophthalmology surgical education; conjunctival closure; video-based curriculum; stepwise teaching method; virtual resident education